A test for within‐lake niche differentiation in the nine‐spined sticklebacks (Pungitius pungitius) - Calboli, Federico C. F. (Ecol Evol, 2016)
Specialization for the use of different resources can lead to ecological speciation. Accordingly, there are numerous examples of ecologically specialized pairs of fish “species” in postglacial lakes. Using a polymorphic panel of single nucleotide variants, we tested for genetic footprints of within‐lake population stratification in nine‐spined sticklebacks (Pungitius pungitius) collected from three habitats (viz. littoral, benthic, and pelagic) within a northern Swedish lake. Analyses of admixture, population structure, and relatedness all supported the conclusion that the fish from this lake form a single interbreeding unit.